A comparative study among medical and nursing interns about the awareness of hepatitis B infection and knowledge of vaccination status: a cross sectional study - Sushma, Marupuri; Musthaq Pasha, M. A.; Fatima, Afsar; Issac Ebenezer, B. (International Journal Of Community Medicine And Public Health, 2017)
Background: Hepatitis B is a major health problem worldwide and more serious in India. An estimated 240 million people are chronically infected with hepatitis B. Hepatitis B is an important occupational hazard for health workers. However, it can be prevented by currently available safe and effective vaccine. A Study on Awareness of Hepatitis B Infection and Vaccination among Medical Interns and Nursing interns in Santhiram Medical College, Nandyal, Kurnool, Andhra Pradesh. Methods: A cross-sectional comparative study is done. Students who are present at the time of data collection by a pre structured pre-tested questionnaire given. Data was analyzed by usingSPSS 21 version. Data was presented in proportions and chi-square was done for significance with 95% confidence interval. Results: The study was under taken among the medical interns (80) and nursing interns (70) at Santhiram Medical College, Nandyal. Out of all 150 students 87% all know that the type of infections viral. There is a significant knowledge difference between the medical interns and nursing interns about the knowledge of the modes of transmission i.e. Medical interns have higher knowledge when compared to nursing interns. 97% of medical interns are vaccinated whereas only 50% of nursing interns and also significant difference knowledge about the post exposure prophylaxis 76% in medical interns 19% in nursing interns. Conclusions: This study showed that overall awareness regarding hepatitis B is at a very basic level among the nursing interns when compared to medical interns of the future and measures need to be taken to create complete awareness.